2013
DOI: 10.1007/s00726-013-1603-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol mixed with energy drink and alcohol alone on subjective intoxication

Abstract: Recent studies suggest that the combination of caffeine-containing drinks together with alcohol might reduce the subjective feelings of alcohol intoxication—the so-called “masking effect”. In this study, we aimed to review the effects of alcohol in combination with caffeine or energy drink with special focus on the “masking effect”. Fifty-two healthy male volunteers were analysed concerning breath alcohol concentration and subjective sensations of intoxication using a 18 item Visual Analogue Scale in a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
1
10
1
1
Order By: Relevance
“…It can be questioned to what extent these four symptoms (i.e., higher scores of headache, weakness, salivation, and reduced motor coordination) are related to subjective intoxication and masking. Of note, Ferreira's findings were not confirmed in a recent replication study with twice the number of subjects (Ulbrich et al, 2013). In this study, Ulbrich et al (2013) found no significant difference on any of the 18 symptoms that were examined by Ferreira et al (2006).…”
Section: Does Mixing Alcohol With Energy Drink Change the Drinker'scontrasting
confidence: 86%
See 1 more Smart Citation
“…It can be questioned to what extent these four symptoms (i.e., higher scores of headache, weakness, salivation, and reduced motor coordination) are related to subjective intoxication and masking. Of note, Ferreira's findings were not confirmed in a recent replication study with twice the number of subjects (Ulbrich et al, 2013). In this study, Ulbrich et al (2013) found no significant difference on any of the 18 symptoms that were examined by Ferreira et al (2006).…”
Section: Does Mixing Alcohol With Energy Drink Change the Drinker'scontrasting
confidence: 86%
“…Of note, Ferreira's findings were not confirmed in a recent replication study with twice the number of subjects (Ulbrich et al, ). In this study, Ulbrich et al () found no significant difference on any of the 18 symptoms that were examined by Ferreira et al (). Similarly, Alford, Hamilton‐Morris, and Verster () could not find significant differences in subjective effects to support the findings of Ferreira et al…”
Section: Resultsmentioning
confidence: 80%
“…Except for one study (Peacock et al ., ), it was consistently found that “stimulation” ratings after consuming alcohol plus caffeine were not significantly different from alcohol plus placebo (Fillmore, ; Marczinski and Fillmore, ; Attwood et al ., ; Marczinski et al ., ; Marczinski et al ., ; Marczinski et al ., ; McKetin and Coen, , Heinz et al ., , Benson and Scholey, ). Similarly, no significant effect of alcohol plus caffeine was found on “sedation” ratings (Benson and Scholey, ; Fillmore, ; Marczinski et al ., ; Marczinski et al ., ; Marczinski et al ., , Marczinski and Fillmore, ; McKetin and Coen, ; Peacock et al ., ; Heinz et al ., ), and with only few exceptions (Drake et al ., ; Marczinski et al ., ; Smith, ), the vast majority of studies did not find significant effects of alcohol plus caffeine (versus alcohol only) on various subjective assessments related to sleepiness and alertness (Alford et al ., ; Attwood et al ., ; Ferreira et al ., ; Ulbrich et al ., ; Azcona et al ., ; Benson and Scholey, ; Liguori and Robinson, ; Peacock et al ., ; Marczinski et al ., ; Peacock et al ., ). In case significant differences were found (Drake et al ., ; Marczinski et al ., ; Smith, ), like in the current study the effects were small and had no clinical relevance.…”
Section: Discussionmentioning
confidence: 98%
“…While these data provides the first overview of physiological and psychological outcomes after ED with illicit stimulant use, causal attributions cannot be drawn as side‐effects of the substances consumed independently were not assessed. Laboratory studies have generally shown similar ratings of physiological outcomes after administration of alcohol with and without ED [32–34], suggesting that negative effects may be primarily driven by alcohol consumption, although low doses of ED (∼250 mL) were administered relative to retrospective self‐reported real‐world intake (∼500–750 mL) and consumer retrospective self‐report indicates greater odds of stimulant, and lower odds of sedation‐based, side‐effects [12]. It is important to note that the typical ED volume co‐ingested with alcohol was in excess of Australian recommended maximum daily intake guidelines [25].…”
Section: Discussionmentioning
confidence: 99%